Strategies for Success With Umbilical Cord Haematopoietic Stem Cell Transplantation in Children With Malignant and Non-Malignant Disease Indications - Wynn, Rob; Nataraj, Ramya; Nadaf, Rubiya; Poulton, Kay; Logan, Alison (Frontiers in Cell and Developmental Biology, 2022)
Umbilical Cord blood (UCB) is an intuitively attractive stem cell source, but its use has declined since it is associated with an increased procedure-related morbidity and transplant related mortality. Some of this reflects that cord blood transplants are more often HLA-mismatched compared to other unrelated donor transplants. The ability to transplant in such a setting, indeed without high rates of chronic Graft versus Host Disease (GVHD), constitutes an advantage compared to other unrelated donor cell sources and there are other advantages specifically associated with cord blood as a donor cell source. These advantages must be weighed against its disadvantage, and we have utilised cord blood preferentially as a donor cell source in certain clinical situations in paediatric medicine. In non-malignant diseases, outcomes in metabolic disease are critically dependent on age at transplant and the enzyme delivered by that transplant, and in cord blood transplantation then the time to transplant can be minimised and the engrafted recipients have higher chimerism and hence delivers higher enzyme levels. In malignant diseases, studies have described reduced relapse rate and better GVHD-free survival, and so we have prioritised cord as a donor cell source where the risk of relapse is highest, and the effects of higher TRM is most clearly offset by the reduced relapse rates.